Nurse's activities in the promotion and management of breastfeeding: the living of an academic of nursing (Research, Society and Development, 2021)
Objective: to describe the experiences of a nursing student in the actions to promote breastfeeding during the supervised internship at a public maternity hospital in Manaus. Description of experience: This is a descriptive study, an experience report, elaborated in the context of the discipline Women's Health and Supervised Internship. Results: The knowledge of the nurse and the nursing team about the advantages of breastfeeding are paramount, this knowledge can determine all professional conduct and interfere in the search for strategies that aim at the promotion and proper management of breastfeeding. Final considerations: It can be considered that the activity was super successful, because through the experience lived together with the pregnant women and puerperas it was possible to gain a greater perception of the extreme importance of the nurse's role in breastfeeding.